Sign Language Detection using Deep Learning (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we put forward a system that bridges the gap between people who use Sign Language tocommunicate and the computer. Sign Language Recognition systems, though much crucial, suffer the lack of implementationin our common day to day devices. This paper focuses on various techniques and tools to help resolve this gap using DeepLearning. Here we propose a system that recognizes sign language and predicts the right sign using a web camera. Thesystem uses Deep learning techniques, Convolution neural networks, max pooling and ReLU activation function. We aim tocreate a software which is both affordable, much more accessible to the users and works without compromising with thedesired results.